Intersections between Diplomacy and Philosophy: Athens, Rome - Aleknienė, Tatjana (Problemos, 2020)
The political context of Greek philosophy and its political themes are the subject of numerous studies, but the relation between diplomacy and philosophy, to the best of my knowledge, has not yet been studied. In this article I examine two episodes of diplomatic missions that have left a clear mark on the history of philosophy and I try to show that the link between the history of diplomacy and the history of philosophy is neither accidental nor superficial.
Keywords: diplomacy; history of philosophy; rhetoric; philology; sophistic